Investigating Students’ Understanding of Complex Number and Its Relation to Algebraic Group Using and APOS Theory - Idowu Oluwaseun Longe; Aneshkumar Maharaj (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
This study focused on students’ inability to correctly use psychometric tests applied for complex numbers in the context of generating an Algebraic abelian group (closure, commutative, associatively, inverse, and identity). This was done using a psychometric test (Kuder and Richardson formula) and APOS Theory after they had been taught the relevant content. The 41 participants were second-year students in the Department of Statistics at the Federal Polytechnic Ile-Oluji. They were given a class test comprising eleven (11) objective questions, and 4 questions relating to group theory were extracted for this analysis. After that, six (6) students were interviewed to gain insight into their perspectives. It was observed that most of the students had difficulty understanding the concept of algebraic groups about complex numbers, founded on not seeing the relevance in the prerequisite knowledge of an algebraic group. Also, if the reliability test of the question is unacceptable, then a good percentage of the participant lacked the mental construction relating to APOS to answer such a question. Keywords: Complex Number, Algebraic group, Prerequisite, Difficulty, Discrimination index, Psychometrics.